2002
DOI: 10.1038/sj.bjc.6600051
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of specialist genetic assessment: psychological impact on women at different levels of familial breast cancer risk

Abstract: The aim was to compare the psychological impact of a multidisciplinary specialist genetics service with surgical provision in women at high risk and those at lower risk of familial breast cancer. Women (n=735) were randomized to a surgical consultation with (trial group) or without (control group) specialist genetic risk assessment and the possible offer of presymptomatic genetic testing. Participants completed questionnaires before and immediately after the consultation to assess anxiety, cancer worry, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
3
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 35 publications
(33 reference statements)
8
86
3
1
Order By: Relevance
“…Unlike previous research that found significant reductions in cancer worry only for those women at low or moderate risk of breast cancer (i.e. Brain et al, 2002), reductions in cancer worry in the present study were not dependent on objective risk.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Unlike previous research that found significant reductions in cancer worry only for those women at low or moderate risk of breast cancer (i.e. Brain et al, 2002), reductions in cancer worry in the present study were not dependent on objective risk.…”
Section: Discussioncontrasting
confidence: 55%
“…Secondary analysis of the data (Brain et al, 2002) showed some significant differences in psychological outcomes between groups of women at different levels of breast cancer risk. Only those women at low or moderate risk showed significant reductions in cancer worry and perceived risk of breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 There are few data on models of service delivery 8 and, until recently, there have been few randomised controlled trials (RCTs) in the clinical genetics arena. One UK randomised trial 9 found no differences in psychological outcomes (anxiety, cancer worry, perceived risk, interest in genetic testing and satisfaction) when comparing a multidisciplinary specialist genetics service with surgical provision for women at familial risk for breast cancer. Although this study described the health professionals involved in providing the two services, and some details about the interventions offered, the process attributes of the services compared, such as waiting times, proximity, length of consultation and so on were not clear.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Information is required about cancers in maternal and paternal relations, as well as details of unaffected relatives. Upon this data, risk estimates are calculated -average (ie population), moderate or high risk -and decisions taken, such as reassurance, surveillance, genetic testing or prophylactic surgery.…”
Section: Introductionmentioning
confidence: 99%